Standalone totally thoracoscopic left appendage exclusion for stroke prevention and absolute contraindication to anticoagulation: a referral centre experience. (25th November 2020) - Branzoli, S; Guarracini, F; Pederzolli, C; Pomarolli, C; D'Onghia, G; Centonze, M; Casagranda, G; Sarubbo, S; Fantinel, M; Bonmassari, R; Graffigna, A; La Meir, M; et al.
Abstract: Introduction: Left atrial appendage is the source of more than 90% of thrombi in patients with atrial fibrillation (AF). ESC guidelines state as class IIB indication left appendage exclusion in patients with contraindication to oral anticoagulation. Here we give our contribute to the issue of safety and efficacy of standalone totally thoracoscopic left appendage exclusion (TT-LAE) for stroke prevention in patients with contraindication to oral anticoagulant or at risk of life threatening hemorrhage on antiplatelet therapy: a large single Centre experience. Materials and methods: 60 patients with non valvular AF and contraindication to oral anticoagulation (25 cerebral hemorrhages, 8 GI bleeding, 18 non cerebral/Gi bleeding requiring multiple transfusions, 2 myelodysplastic syndrome, 7 anatomy unsuitable for percutaneous closure, 75%male, patients age ranged 53–87 years, mean CHAD-VASC 6.4, mean HASBLED range 4.7, type of AF permanent 76.6%, 23.4% longstanding persistent), underwent stand alone totally thoracoscopic appendage exclusion. All patinets enrolled after Heart Team evaluation, were screened preoperatively with 3D CT scan, transesophageal echocardiography, spirometry and cerebrovascuar doppler ultrasound. Intraoperative appendage exclusion were guided and confirmed by transesophageal echo. All patients were not on anticoagulation nor antiplatelet therapy at the time of surgery, at discharge and at control visit. Follow up (range 35–1 months) included outpatient visit and CT scan or TEE at 3–6-12 month in all patients to document LAA exclusion. Perioperative mortality and early and late morbidity in addition to freedom from neurological events at follow up were analyzed by chart evaluation and full outpatient neurological examination including including the Questionnaire for Verifying Stroke Free Status (QVSFS) as validated screening tool. Results: Mean duration of surgery "skin to skin" was 52.4 minutes; all patients were extubated shortly after the procedure. There were no deaths nor need for blood transfusion or pulmonary procedure related morbidities, only three casea of pericarditis treated with colchicine till complete resolution was documented. On CT or TEE follow up 100% of patients had complete exclusion of the left appendage with minimal residual stumps and no dislodgement of the clip detected. Freedom from neurological events in all patients was documented in absence of anticoagulation or antiplatelet regime from the time of surgery to the time of the follow up visit and questionnaire filling. Conclusion: Standalone totally thoracoscopic left appendage clipping is a safe and effective procedure for stroke prevention in patients with permanent and longstanding persistent atrial fibrillation with contraindication to oral anticoagulation. Longer follow up and an European registry are needed to, possibly, confirm this preliminary results. Funding Acknowledgement: Type of funding source: None